2015
DOI: 10.1371/journal.pone.0120426
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin Inhibits Glucose Uptake and Cooperates with Glycolysis Inhibitor to Induce Apoptosis in Non-Small Cell Lung Carcinoma Cells

Abstract: Despite recent advances in the therapy of non-small cell lung cancer (NSCLC), the chemotherapy efficacy against NSCLC is still unsatisfactory. Previous studies show the herbal antimalarial drug dihydroartemisinin (DHA) displays cytotoxic to multiple human tumors. Here, we showed that DHA decreased cell viability and colony formation, induced apoptosis in A549 and PC-9 cells. Additionally, we first revealed DHA inhibited glucose uptake in NSCLC cells. Moreover, glycolytic metabolism was attenuated by DHA, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 45 publications
0
38
1
1
Order By: Relevance
“…S2). Although previous papers have also shown that NaBu downregulates cell cycle‐associated gene expression in other cell lines or species , the ranges of expression downregulation and the number of downregulated genes are relatively lower than ours. A possible explanation for that might contribute to the cell type‐dependent response to NaBu treatment.…”
Section: Discussioncontrasting
confidence: 92%
“…S2). Although previous papers have also shown that NaBu downregulates cell cycle‐associated gene expression in other cell lines or species , the ranges of expression downregulation and the number of downregulated genes are relatively lower than ours. A possible explanation for that might contribute to the cell type‐dependent response to NaBu treatment.…”
Section: Discussioncontrasting
confidence: 92%
“…Mi et al. first reported a series of glucose metabolism‐related effects of artemisinin in NSCLC cell lines . These effects included an inhibition of glucose uptake and a corresponding attenuation of glycolytic metabolism in the form of suppressed ATP and lactate production.…”
Section: Molecular Targets and Signaling Pathways Implicated In The Amentioning
confidence: 64%
“…Cells were fixed with methanol and stained with 0.5% crystal violet for 20 minutes; visible colonies were counted. Triplicate wells were measured for each group [23].…”
Section: Colony Formation Assaymentioning
confidence: 99%